Las actividades lúdicas y su incidencia en la disgrafía en niños escolares de la Unidad Educativa “Fernando Daquilema”, Riobamba, periodo 2022-2023. - Aucatoma Quishpe, Anderson David (2024)
The present research addressed the topic about play activities and their impact on the prevention of the development of dysgraphia in school children, dysgraphia being a learning disorder, which limits a correct writing, is characterized by a low readability, dullness at the time of using the pencil that notes poor control of the graphic gesture, which influences in not being able to write a text properly, also has an impact in the demotivation of the child, causing a low self-esteem. The main objective of the research is to analyze the impact of play activities as a didactic strategy to reduce dysgraphia in the children of the Educational Unit “Fernando Daquilema”, Riobamba. A methodology with a quantitative approach of pre-experimental design with the same deductive method was proposed that allowed to draw a general conclusion from the research. The inductive method by which the established population was studied was used as well as the analytical method where the disaggregation of information was obtained. For the data collection the Test Purdue pegboard was applied itself which helps to identify the fine motor skills deficit. Among the achievements achieved with this research it can be said that the application of play activities focused on fine motor skills contributes to improving their fine motor skills, their mobility and the writing of children with dysgraphia problems. Similarly, the Test Purdue pegboard was of great contribution to this study, with the purpose of identifying the deficiencies of fine motor skills as it was also applied after the intervention of these activities demonstrating that the problem had a solution for the prevention of dysgraphia.